Efficacy of Ultrasono-Guided Caudal Epidural Steroid in Lumbar Disc Prolapse (KYAMC Journal, 2020)
Background: Ultrasono-guided caudal epidural steroid injections are used for the treatment of radicular lumbosacral pain syndromes with the safest, easiest, and minimal risk.Objective: The study is to show efficacy of ultrasono-guided caudal epidural steroid in acute and chronic low back pain due to prolapsed lumbar intervertebral disc (PLID).Materials and Methods: Thirty consecutive patients with acute and chronic low back pain with radiculopathy and without red flag sign where clinical diagnosis were prospectively included in this study in Popular Medical College Hospital, Dhanmondi, Dhaka.Results: The mean age was 40.83±13.34 (mean± SD). Male and female ratio was 3:2. Regarding diagnosis, 56.66% were acute and 43.33% were chronic low back pain in which 40% had lumbar canal stenosis, 70% had right sided radiation, 20% had left sided radiation and 10% had bilateral radiation. After 4 weeks, most of the study population was significantly improved regarding Visual Analogue Scale (VAS) score in lumbar pain and radiation pain, tenderness over lumbar spine, Straight Leg Raising (SLR) test and improvement of mean difference ± Standard Deviation (SD) after 4 weeks were 4.25±3.12, 4.58±1.58, 1.7±0.92 and 29.5±16.15 accordingly. Functional improvement of Oswestry Disability Index (ODI) from baseline 39.60±7.11 to 15.67±0.96. Mean difference of all variables were statistically significant.Conclusion: Ultrasound is an effective tool, not only to guide the insertion of the needle into the caudal epidural space, but also to predict the procedural success rate.KYAMC Journal Vol. 11, No.-2, July 2020, Page 67-72